Periode Deformasi Kenozoikum Kepulauan Aru, Cekungan Wokam, Maluku - Iwan Sukma Gumilar (Pusat Survei Geologi, 2017)
Research on structural geology to determine deformation periodes at the Aru Islands of Wokam Basin, Maluku have been done. Determaining the deformation periodes are approached by grouping the lineament structure and stress tensor analysis of bedding, joints, slicken side data which collected during fieldwork. The age of structural geology which formed at these area are reconstructed from stratigraphic relationship of deformed rocks. At Cenozoic, the deformation of Aru Islands, Maluku can be divided into three main periodes which have different characteristic and geological structures pattern. The first periode were started at Late Miocene where the Koba Formation had been deposited, the main stress direction was Northwest-Southeast and the stress tensor tend to pure strike-slip. The second periode occured after Manumbai Formation were deposited at Late Pleistocene, the main stress was extentional and yielded normal faults as fault reactivation. At B the third periode take place and generated North-South structural lineations.Â Keywords : deformation, Cenozoic, geological structures, AruIslands.